Optimal sizing and feasibility analysis of second-life battery energy storage systems for community microgrids considering carbon reduction - Terkes, Musa; Ozturk, Zafer; Demirci, Alpaslan; Tercan, Said Mirza (ELSEVIER SCI LTD, 2023)
The rapid development of distributed renewable energy has made energy storage essential for efficient operation. However, energy storage is challenging for prosumers due to high investment costs and long payback periods. The second use of batteries has been evaluated as an alternative energy storage after the first service in electric vehicles with the remaining 80% capacity. This study investigates the feasibility of using secondary-use batteries as shared storage for prosumers. Financial and technical break-even points regarding the gradually increasing carbon limit on the way to 100% renewable have been determined. The proposed method's performance has been verified by conducting sensitivity analyses regarding various environmental and economic characteristics. The self-consumption rates have been achieved by 65.9% in Spain (Madrid) and 49.9% in England (London), and 48.5% in Turkiye (Antalya) without incentive. Increasing the carbon tax by 1 $/t for high and low energy tariffs can reduce carbon emissions by 181.3 and 1607 kg/yr. The optimum sizes remain until the carbon tax threshold is 60 $/tCO2eq for high energy tariffs. After 60 $/tCO2eq, it is tended to enlarge the hybrid power system. However, severe carbon emission restriction for zero carbon targets prevents the optimum system design since the carbon reduction cost increases to 232.7-304.8 $/kg. This study encourages investors and prosumers to plan the shared energy storage system sensibly and guides governments to develop realistic incentive mechanisms to implement second-life batteries effectively.
Keywords: Energy storage; Hybrid energy system; Photovoltaics; Optimization; Second-life battery; RENEWABLE ENERGY; SOLAR PHOTOVOLTAICS; OPTIMAL-DESIGN; COST; IMPACTS; LITHIUM; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology